If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 21 = 13x + -49 Reorder the terms: 21 + 6x = 13x + -49 Reorder the terms: 21 + 6x = -49 + 13x Solving 21 + 6x = -49 + 13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13x' to each side of the equation. 21 + 6x + -13x = -49 + 13x + -13x Combine like terms: 6x + -13x = -7x 21 + -7x = -49 + 13x + -13x Combine like terms: 13x + -13x = 0 21 + -7x = -49 + 0 21 + -7x = -49 Add '-21' to each side of the equation. 21 + -21 + -7x = -49 + -21 Combine like terms: 21 + -21 = 0 0 + -7x = -49 + -21 -7x = -49 + -21 Combine like terms: -49 + -21 = -70 -7x = -70 Divide each side by '-7'. x = 10 Simplifying x = 10
| 2x+13=-13 | | 6x+5+x= | | 8x+12=-132 | | 9x-34=3x+2 | | 6p+1=(2p+1) | | 8(1+3n)+n(-4n+4)= | | 11x+1=9x+15 | | 4(5+4n)-3(1+6n)= | | 5x-5=50 | | 2x+4(-6+10)=-16x+4(-8-14) | | n(-8n+8)+5(n-1)= | | -7m(3m+7)+3(m+1)= | | -4-0.7m=2.3 | | 75=-5(a+5) | | -4p(2p+2)+4p(2-2p)= | | 6.5=2x+4.1 | | 3(x+8)=-6 | | 6(-3+8x)-(3x-3)= | | 3(6+x)=27 | | 2(11-4x)=38 | | -3(7r-6)+8(5r+5)= | | 24-(-21)+7-(-3)= | | 5k(3k-3)+6k(1-6k)= | | 19x-69=45 | | 14x-6-11x=21 | | n-3(5-8n)= | | -6(4-v)-2v= | | n-10+9+9n= | | -8(1-8x)-4= | | 2(-x-1)+8x= | | -90-36= | | 1+3x-9= |